Spirometric assessment of the rural population of Rejowiec Commune - Sagan, Michał; Warchulińska, Joanna; Dec-Szlichtyng, Mariola; Lupa, Krystyna; Jakubiak, Monika (Polish Journal of Public Health, 2010)
Introduction. Lung function tests are the oldest methods used to measure the air volume and capacities of the lungs. Such tests make it possible to diagnose respiratory disorders, localize them, assess their dynamics and reversibility, as well as set forth the conclusive prognoses. Aim. The aim of this study was to perform a screening spirometric examination among a chosen population with an indication for further diagnostic action and health education in the sphere of chronic diseases of the respiratory system. Material and method. The examinations covered a group of 273 adult inhabitants of Rejowiec Commune. The measurements were taken with the use of a portable MicroLab Spiro apparatus. The reference values in accordance with the American Thoracic Society (ATS) were used for the evaluation of the spirometric results. Results. The analysis of the mean values of individual spirometric parameters in relation to sex shows slightly higher values of FEV1, FVC, FEV1%FVC for women. For men, higher values were assessed for PEF%, MEF50%, and MEF25% (p